Notes on Early Land Plants Today. 37. Towards a stable, informative classification of the Lepidoziaceae (Marchantiophyta) - Cooper, Endymion D. (Phytotaxa, 2013)
Recent molecular phylogenies of the Lepidoziaceae indicate that the current classification is incongruent with the phylogeny. Although substantial uncertainties remain, an interim classification is needed. The classification proposed includes a broader definition of the Lembidioideae, reinstatement of Neolepidozia and Tricholepidozia and the recognition of the new genus Ceramanus. While the Zoopsidoideae are unlikely to represent a monophyletic group, it is not yet possible to provide a phylogenetically accurate revision of this subfamily.